Development of LXR inverse agonists to treat MAFLD, NASH, and other metabolic diseases - Griffett, Kristine; Burris, Thomas P. (Frontiers in Medicine, 2023)
Activation of LXR activity by synthetic agonists has been the focus of many drug discovery efforts with a focus on treatment of dyslipidemia and atherosclerosis. Many agonists have been developed, but all have been hindered due to their ability to efficaciously stimulate de novo lipogenesis. Here, we review the development of LXR inverse agonists that were originally optimized for their ability to enable recruitment of corepressors leading to silencing of genes that drive de novo lipogenesis. Such compounds have efficacy in animal models of MAFLD, dyslipidemia, and cancer. Several classes of LXR inverse agonists have been identified and one is now in clinical trials for treatment of severe dyslipidemia.